Predicting the Trajectory of a Relativistic Electron Beam for External Injection in Plasma Wakefields. (July 2020) - Asmus, F. Peña; Velotti, F. M.; Turner, M.; Gessner, S.; Martyanov, M.; Bracco, C.; Goddard, B.; Muggli, P.
Abstract: We use beam position measurements over the first part of the AWAKE electron beamline, together with beamline modeling, to deduce the beam average momentum and to predict the beam position in the second part of the beamline. Results show that using only the first five beam position monitors leads to much larger differences between predicted and measured positions at the last two monitors than when using the first eight beam position monitors. These last two positions can in principle be used with ballistic calculations to predict the parameters of closest approach of the electron bunch with the proton beam. In external injection experiments of the electron bunch into plasma wakefields driven by the proton bunch, only the first five beam position monitors measurements remain un-affected by the presence of the much higher charge proton bunch. Results with eight beam position monitors show the prediction method works in principle to determine electron and proton beams closest approach within the wakefields width (<1 mm), corresponding to injection of electrons into the wakefields. Using five beam position monitors is not sufficient.